(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Social media has become an integral part of young adults’ lives, influencing self- perceptions and body image. Medical students, given their academic pressures and constant digital connectivity, represent a particularly vulnerable group. Objective: This study aimed to examine the association between patterns of social media use and body image perceptions among undergraduate medical students at Rama Medical College and Hospital, Kanpur. Methods: A cross-sectional, questionnaire-based study was conducted among 480 undergraduate medical students aged 18–25 years. Data were collected using a structured sociodemographic proforma, the Social Media Use Scale (SMUS), and the Body Self-Image Questionnaire–Short Form (BSIQ-SF). Descriptive statistics were used to summarise demographic characteristics, independent t-tests were applied for gender-based comparisons, and Pearson’s correlation was used to assess associations between SMUS and BSIQ-SF domains. A p-value < 0.05 was considered statistically significant. Results: Female students scored significantly higher in comparison-based (23.10 ± 3.25 vs. 20.12 ± 3.45, p < 0.001) and image-based social media use (24.21 ± 3.40 vs. 19.86 ± 3.12, p < 0.001). They also reported higher dissatisfaction across body image domains, including Fatness Evaluation (15.92 ± 3.05 vs. 13.76 ± 2.70, p < 0.001), Negative Affect (17.40 ± 3.12 vs. 14.58 ± 2.85, p < 0.001), and Social Dependence (13.95 ± 2.48 vs. 12.20 ± 2.25, p < 0.001). Correlation analysis showed that comparison-based and image-based social media use were significantly associated with negative body image outcomes, such as lower Overall Appearance Evaluation (r = –0.32, p = 0.001) and higher Negative Affect (r = 0.44, p < 0.001). Consumption-based use demonstrated weaker associations, while belief-based use showed no significant correlations. Conclusion: Social media, particularly comparison-based and image-based use, plays a significant role in shaping body image perceptions among medical students, with females disproportionately affected. These findings highlight the need for awareness programs, psychoeducation, and media literacy interventions in medical colleges to promote healthier social media engagement and foster positive body image. Longitudinal research incorporating objective measures, such as screen-time tracking and BMI, is recommended to further clarify causal pathways.